2019
DOI: 10.1534/g3.119.400445
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Karyotyping of Chromosomally Polymorphic Malaria Mosquitoes in the Anopheles gambiae Complex

Abstract: Chromosomal inversion polymorphisms play an important role in adaptation to environmental heterogeneities. For mosquito species in the Anopheles gambiae complex that are significant vectors of human malaria, paracentric inversion polymorphisms are abundant and are associated with ecologically and epidemiologically important phenotypes. Improved understanding of these traits relies on determining mosquito karyotype, which currently depends upon laborious cytogenetic methods whose application is limited both by … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 72 publications
(107 reference statements)
1
44
0
Order By: Relevance
“…Previous work has shown that applying candidate tags to a taxon in which they are not 459 valid has the effect of downwardly biasing the average number of inferred alternate 460 alleles (Love et al 2019). Consistent with this, if 2Rd tags in the present study were 461 inappropriately applied to An.…”
supporting
confidence: 76%
See 4 more Smart Citations
“…Previous work has shown that applying candidate tags to a taxon in which they are not 459 valid has the effect of downwardly biasing the average number of inferred alternate 460 alleles (Love et al 2019). Consistent with this, if 2Rd tags in the present study were 461 inappropriately applied to An.…”
supporting
confidence: 76%
“…Beginning with a ranked list of tags based on descending genotypic concordance, 212 we applied filters (described below) that narrowed the numbers of tags based on design 213 criteria unique to each platform. To ensure that we retained at least six tag SNPs per inversion for genotyping, we were 235 compelled to reduce the genotypic concordance threshold below the 0.8 level imposed 236 in Love et al (2019). Even lowering the threshold to 0.7 for 2Rc tags in An.…”
Section: Oa and Gt-seq Assay Design And Genotyping 197mentioning
confidence: 99%
See 3 more Smart Citations